Exploring attributional and coping strategies in competitive injured athletes: a qualitative approach - Leguizamo, Federico; Núñez, Antonio; Gervilla, Elena; Olmedilla, Aurelio; Garcia-Mas, Alejandro (Frontiers in Psychology, 2023)
Introduction This study explores the attributions and coping strategies of athletes who experienced psychological impact from sport injuries or illness from a qualitative methodology. Purpose To understand athletes' unique perspectives on injury and recovery, framed in the Global Model of Sport Injuries, and contribute to the development of effective interventions and support programs for athletes. Methods A qualitative research approach was employed, conducting semi-structured interviews with an ad hoc sample of 16 athletes, representing diverse backgrounds and competitive levels. Interviews were transcribed and analyzed using NVivo software, identifying themes and codes related to attributions and coping strategies. Results Athletes attributed their sport injury mostly to bad luck, routine deviations, and negative mental states, while coping strategies used included cognitive restructuring, emotional calming, seeking social support, mental withdrawal, and behavioral risk. Factors such as training deviations, social support, psychological responses, and injury diagnosis seems to have influenced the coping strategies employed. Conclusions Sport injuries and illnesses significantly impact athletes' careers and wellbeing. Support and effective communication from coaching staff and healthcare professionals were identified as crucial for athletes' wellbeing. These findings contribute to understanding the psychological processes and experiences involved in sport injury recovery and highlight key elements for prevention and intervention protocols. Future research should explore communication patterns in sports contexts and assess attributions and coping strategies at different stages of injury recovery.